2017
DOI: 10.1159/000470915
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia Severity Assessment Tools for Predicting Mortality in Patients with Healthcare-Associated Pneumonia: A Systematic Review and Meta-Analysis

Abstract: Background: In contrast to community-acquired pneumonia (CAP), no specific severity assessment tools have been developed for healthcare-associated pneumonia (HCAP) in clinical practice. Objectives: In this review, we assessed the clinical significance of severity assessment tools for HCAP. Methods: We identified related articles from the PubMed database. The eligibility criteria were original research articles evaluating severity scoring tools and reporting the outcomes of mortality in patients with HCAP. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
(128 reference statements)
3
15
0
Order By: Relevance
“…The use of different inclusion criteria and management strategies, combined with different outcome measures used in previous studies, makes direct comparison with our findings challenging. The AUROC for the CURB65 has been reported as ranging from 0.717 to 0.8298 28 33 in CAP populations (with patients with HCAP excluded), to 0.6534 in a cohort which included patients with HCAP, similar to findings presented here. The use of CURB65 in the HCAP population has been validated previously by Ewig et al 35…”
Section: Discussionsupporting
confidence: 85%
“…The use of different inclusion criteria and management strategies, combined with different outcome measures used in previous studies, makes direct comparison with our findings challenging. The AUROC for the CURB65 has been reported as ranging from 0.717 to 0.8298 28 33 in CAP populations (with patients with HCAP excluded), to 0.6534 in a cohort which included patients with HCAP, similar to findings presented here. The use of CURB65 in the HCAP population has been validated previously by Ewig et al 35…”
Section: Discussionsupporting
confidence: 85%
“…PSI is known as a useful tool for predicting mortality in CAP patients, but the predictive power of PSI for mortality in NHCAP patients is insufficient. Chalmers et al showed that the AUC using cut‐off values of ≥4 was 0.82 for the PSI score for evaluating the prediction of mortality in CAP patients in systematic reviews, whereas the AUC using cut‐off values of ≥4 was 0.68 (0.64–0.72) for the PSI score in HCAP patients in our previous systematic review . This present study showed that PSI might be more useful for predicting pneumonia‐related mortality than A‐DROP and I‐ROAD in NHCAP patients, but the predictive power seems insufficient for predicting mortality in NHCAP patients.…”
Section: Discussionmentioning
confidence: 44%
“…Chalmers et al showed that the AUC using cut-off values of ≥4 was 0.82 for the PSI score for evaluating the prediction of mortality in CAP patients in systematic reviews, 14 whereas the AUC using cut-off values of ≥4 was 0.68 (0.64-0.72) for the PSI score in HCAP patients in our previous systematic review. 15 This present study showed that PSI might be more useful for predicting pneumonia-related mortality than A-DROP and I-ROAD in NHCAP patients, but the predictive power seems insufficient for predicting mortality in NHCAP patients. Furthermore, PSI score is not widely used in clinical settings in Japan because of its relative complexity and the lack of physicians' awareness in addition to its weak power for predicting mortality in NHCAP patients.…”
Section: Discussionmentioning
confidence: 50%
“…Compared with CURB-65, PORT “identifies larger proportions of patients as low risk and has a higher discriminative power in predicting mortality” [ 9 ]. However, PORT scoring is not frequently used in everyday clinical practice, possibly due to its complexity or lack of physician awareness [ 17 , 18 ]. Therefore, the guidelines also acknowledge the simplicity of the CURB-65 score and recommend it as an alternative for site-of-care decision making, despite the lower quality of evidence regarding its use.…”
Section: Discussionmentioning
confidence: 99%